Dal razionalismo critico al problematicismo pedagogico. Considerazioni e spunti di ricerca - Trebisacce, Giovambattista (Studi sulla Formazione/Open Journal of Education, 2013)
The origins of critical problematicism are in the Antonio Banfi’s thought, who uses Neokantianism, Phenomenology, Maxism with an advanced device. By Giovanni Maria Bertin the problematicism applies to pedagogy, developing by its pupils in Bologna and offering an actual model of philosophy of education.